Novel HLA allele associations with susceptibility, staging, symptomatic state, autoimmune hepatitis and hepatocellular carcinoma events for primary biliary cholangitis in the Japanese population - Khor, Seik-Soon; Ueno, Kazuko; Nishida, Nao; Kawashima, Minae; Kawai, Yosuke; Aiba, Yoshihiro; Hitomi, Yuki; Nagasaki, Masao; Nakamura, Minoru; Tokunaga, Katsushi (Frontiers in Immunology, 2023)
Primary biliary cholangitis (PBC) is a rare autoimmune disease with a clear predisposition for human leukocyte antigen (HLA)-DR/DQ-associated loss of immune tolerance for the E2 component of the pyruvate dehydrogenase complex. Three-field-resolution HLA imputation of 1,670 Japanese PBC patients and 2,328 healthy controls was conducted using Japanese population-specific HLA reference panels. Eighteen previously reported Japanese PBC-associated HLA alleles were confirmed and extended to 3-field-resolution, including HLA-DRB1*08:03 to HLA-DRB1*08:03:02, HLA-DQB1*03:01 to HLA-DQB1*03:01:01, HLA-DQB1*04:01 to HLA-DQB1*04:01:01 and HLA-DQB1*06:04 to HLA-DQB1*06:04:01. In addition, additional significant novel HLA alleles were identified, including 3 novel susceptible HLA-DQA1 alleles: HLA-DQA1*03:03:01, HLA-DQA1*04:01:01, HLA-DQA1*01:04:01 and 1 novel protective HLA-DQA1 allele, HLA-DQA1*05:05:01. In addition, PBC patients carrying HLA-DRB1*15:01:01 and HLA-DQA1*03:03:01 would have a higher predisposition toward developing concomitant autoimmune hepatitis (AIH). Further, late-stage and symptomatic PBC shared the same susceptible HLA alleles of HLA-A*26:01:01, HLA-DRB1*09:01:02 and HLA-DQB1*03:03:02. Lastly, HLA-DPB1*05:01:01 was identified as a potential risk HLA allele for development of hepatocellular carcinoma (HCC) in PBC patients. In conclusion, we have extended the current knowledge of HLA allele associations to 3-field resolution and identified novel HLA allele associations with predisposition risk, staging, symptomatic state, and AIH and HCC events for Japanese PBC patients.